CLINICAL FEATURES OF PATIENTS WITH MAXILLARY SINUS CYSTS - Alisher Mukhiddinov; Jamolbek Djuraev; Ilyasjon Soatov (International Journal of Medical Science and Public Health Research, 2025)
Maxillary sinus sinuses cysts was headache in patients many in cases permanent and occasionally with was, but years during his/her intensity increased. Daily in life wide applicable analgesics acceptance to relieve headaches (citramon, analgin, pyramidon, baralgin) eliminate to reach take came.